2019
DOI: 10.1016/j.scitotenv.2019.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in greenhouse gas emissions from French agriculture and livestock (1852–2014): From traditional agriculture to conventional intensive systems

Abstract: • French GHG emissions from agricultural and forest sectors were estimated. • A long-term trajectory (1852-2014) was reconstructed for N 2 O, CH 4 , CO 2. • GHG emissions have grown four-fold since 1852, to 120,000 CO 2 Eq yr −1 in the 2000s. • GHG emissions have only stabilised, in spite of agro-environmental measures. • Deep changes in the agro-food system would reduce agricultural GHG emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 81 publications
(117 reference statements)
0
63
0
Order By: Relevance
“…The above formula is used to calculate PET as a function of this temperature anomaly. In the absence of evidence for significant variation, interannual average pluviometry is considered constant over the whole period, as assumed by Garnier et al (2019). accounted for if, in a given year, agricultural land declined while forest land expanded, considering only net land conversion (Fuchs et al, 2016).…”
Section: Soil Modulementioning
confidence: 99%
“…The above formula is used to calculate PET as a function of this temperature anomaly. In the absence of evidence for significant variation, interannual average pluviometry is considered constant over the whole period, as assumed by Garnier et al (2019). accounted for if, in a given year, agricultural land declined while forest land expanded, considering only net land conversion (Fuchs et al, 2016).…”
Section: Soil Modulementioning
confidence: 99%
“…The domestication of megafauna like horses, cattle and sheep is one of the most important developments in human history in the past 13,000 years and a prerequisite to the rise of civilization (Diamond, ). Nowadays, a large portion of human diet originates from intensive livestock farming with adverse effects on global ecosystems, climate as well as animal welfare (Garnier et al, ; Tilman, Cassman, Matson, Naylor, & Polasky, ). Climate change is expected to strongly limit this conventional livestock production (Rojas‐Downing, Nejadhashemi, Harrigan, & Woznicki, ).…”
Section: The Socio‐cultural and Economic Consequences Of The Analogoumentioning
confidence: 99%
“…where net C emissions UAA is the annual average net C emissions from agricultural soil over the 2040-2050 period in region i (tonC-CO 2 ha UAA −1 yr −1 ); Table 3, Garnier et al, 2019) Stock C CL/GL yr i is the simulated SOC stock in cropland or grassland in any year (yr expressed in tonC yr −1 ), obtained as the product of SOC content (tonC ha −1 ) by the corresponding area of cropland or grassland of the region (ha);…”
Section: Sequestration In Soilsmentioning
confidence: 99%
“…Gingrich et al (2007) and Erb et al (2007) have indeed underlined that an increased soil C sequestration was only made possible in the mid-twentieth century owing to an unprecedented use of non-solar energy in agriculture, a phenomenon described as a "fossil-fuel-powered carbon sink." However, Garnier et al (2019) showed that CO 2 emissions account for 22% of the French agricultural greenhouse gas emissions. Therefore, the future challenges of climate change mitigation and food safety needs to account for the systemic effects of the structure of the agro-food system and the legacies left out by the past.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation